An entomopathogen-based small-RNA delivery system promotes the biocontrol efficacy against termites - Chen-Chen Zhao; Hang Lu; Xiao-Long Mao; Long-Long Sun; Fang-Chan He; Zheng-Xun Lv; Qing-Bo Tang; Cheng-Wei Li; Long Liu (Pesticide Biochemistry and Physiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Characterization of rare genomic structural variants across 2,981 genomes reveals significant involvements in recessive conditions - Zirui Dong; Keying Li; Chi Chun Chan; Jia Zheng; Mengmeng Shi; Wenbin He; Matthew Hoi Kin Chau; Ye Cao; Juan Du; Yvonne Ka Yin Kwok; Yue-Qiu Tan; Kwong Wai Choy (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Improving consistency of WRF-UCM-based typhoon wind field simulations with field observations: A sensitivity analysis of model parameters - Yuxin Zhang; Qiusheng Li; Shuyang Cao; Junyi He; P.W. Chan; Lin Zhao; Jinxin Cao (Urban Climate, 2026)

Multi-source observational study of wind shear and veer at Hong Kong International Airport - Yucheng Xue; Junyi He; Pakwai Chan; Qiusheng Li (Urban Climate, 2026)

Paleocene to Eocene deformation and crustal shortening history of the Tanggula Range, Central Tibet - Wenjun Bi; Yalin Li; Zhongpeng Han; Chengshan Wang; Jiawei Zhang; Tiankun Xu; Dawei Lv; Chan Wang; Zining Ma; Haiyang He; Huan Chen (Global and Planetary Change, 2026)

Observational study of atmospheric boundary layer height in Hong Kong based on 20-year multi-source measurements - Yu-Cheng Xue; Jun-Yi He; Pak-Wai Chan; Qiu-Sheng Li (Atmospheric Research, 2026)

Photothermal nanomedicine for glioblastoma: From material design to clinical translation challenges - Chan Li; Hui-Zhe Xu; Xue-Yan Cheng; Xin Yu; Zhi-Qiang Gong; Yi-Jiang He; Ling-Xiao Zhao; Zhan-You Wang (Chemical Engineering Journal, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Spatial characteristics and prediction of tropical cyclone-induced storm surge along the Guangdong and Hong Kong Coast - Qinglan Li; Riaz Ali; Jiali Zhang; Lunkai He; Zhijian Wu; Yongchang Ye; Li Zhang; Pak-Wai Chan (Atmospheric Research, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Synthesis Pathway Oriented Heterogeneous Stacking Mode of Homogeneous Two-Dimensional Hydrazone-Linked COFs - Zhiying Fan; Yingdan Zhang; Ningning He; Yingdi Zou; Jie Zhang; Chan Deng; Meicheng Zhang; Lei Wang; Ning Liu; Yang Li; Lijian Ma (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

In situ desulfurization mechanism of molten salt thermal treatment for waste tires - Qiang Gao; Hongyun Hu; Chan Zou; Yan Ding; Chao He; Xian Li; Hong Yao (Fuel, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Lactate and protein lactylation: the ugly duckling of energy as the sculpture artist of proteins - Linpeng Li; Shanhu Sun; Yi Wu; Jianghuan Lu; Jingcai He; Keshi Chen; Wai-Yee Chan; Xingguo Liu (Science Bulletin, 2023)

Spatial-temporal changes of compound temperature-humidity extremes in humid subtropical high-density cities: An observational study in Hong Kong from 1961 to 2020 - Yueyang He; Zixuan Wang; Hau Man Wong; Guangzhao Chen; Chao Ren; Ming Luo; Yuguo Li; Tsz-cheung Lee; Pak Wai Chan; Janice Ying-en Ho; Edward Ng (Urban Climate, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Investigation of the reaction mechanism regarding thermal treatment of biomass using molten salts: A kinetic study of small molecule gases formation - Jing He; Yuhan Yang; Chan Zou; Qiang Gao; Hongyun Hu; Kai Xu; Xi Li; Hong Yao (Journal of Environmental Chemical Engineering, 2023)

Mixed fermentation with Lactobacillus plantarum, Bifidobacteriµm animalis subsp. lactis and Candida utilis improves the fermentation quality of Hong Suan Tang - Chan Wang; Xiaojuan Song; Cuiqin Li; Laping He; Xiao Wang; Xuefeng Zeng (Food Chemistry, 2023)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Large-scale evaluation of aluminum tolerance in maize (Zea mays L.) acessions - Jianzhou Ding; Wei Yang; Xiaoqi Hu; Weina Yan; Wanpeng Hu; Hongjie Li; Chan Liu; Wenzhu He; Yanli Lu; Shibin Gao; Suzhi Zhang (Theoretical and Experimental Plant Physiology, 2022)

A critical review of microplastic pollution in urban freshwater environments and legislative progress in China: Recommendations and insights - Yuyao Xu; Faith Ka Shun Chan; Jun He; Matthew Johnson; Christopher Gibbins; Paul Kay; Thomas Stanton; Yaoyang Xu; Gang Li; Meili Feng; Odette Paramor; Xubiao Yu; et al. (Critical Reviews in Environmental Science and Technology, 2021)

Dynamic analysis of meteorological time series in Hong Kong: A nonlinear perspective - Bowen Yan; Pak Wai Chan; Qiusheng Li; Yuncheng He; Zhenru Shu (International Journal of Climatology, 2021)
Many meteorological systems are chaotic in nature, which inevitably limits its predictability. Accurate prediction of meteorological variables depends primarily on properly diagnosing the complex underlying dynamics. Nonlinear dynamic analysis has shown to be particularly useful for such purpose. In this study, the concept of recurrence analysis was extended to investigate and characterize the underlying dynamics of meteorological time series (i.e., wind speed, temperature, pressure and relative humidity) based on daily observation in Hong Kong during a period from 1998 to 2018. The existence of chaos was clearly identified based on the phase space reconstruction diagram and the recurrence plot. It was shown that the underlying dynamics associated with wind speed appears to indicate higher level of complexity as compared to those of pressure and temperature, which, in consequence, may lead to more irregular time‐dependent behaviour and lower predictability. Moreover, season‐to‐seasonal variability in the dynamics of meteorological time series was evident, particularly for wind speed and temperature. Overall, this study shows that the recurrence analysis can be well applied as a useful diagnostic tool to investigate the dynamics of meteorological systems, which is expected to provide a new avenue regarding the modelling and prediction of the behaviour of meteorological parameters.

Characterization of daily rainfall variability in Hong Kong: A nonlinear dynamic perspective - Zhenru Shu; Pak Wai Chan; Qiusheng Li; Yuncheng He; Bowen Yan (International Journal of Climatology, 2021)
Modelling and forecasting of rainfall behaviour are of essential importance in various hydrological and meteorological studies, which depends largely on properly understanding the underlying rainfall dynamics. In this paper, 20‐years (i.e., 2000–2019) measurements of daily rainfall data at 6 rain gauge stations in Hong Kong were analysed in the framework of nonlinear dynamic analysis. Phase space reconstruction (PSR), recurrence plot (RP) and recurrence quantification analysis (RQA) were carried out to identify and characterize the chaotic nature of rainfall dynamics. The results of this study underscore the complex processes and variability that is associated with Hong Kong's rainfall data. The existence of chaos in rainfall process was well recognized across various stations. The rainfall dynamics were further investigated with respect to its inter‐annual and monthly variability. The dependence of rainfall dynamics on different temporal scales was likewise examined, which indicates that the rainfall dynamics at finer resolution are less complex than those at coarser resolution, thus the consequent rainfall variability is less pronounced.

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Effects of Soil Amendments on Microbial Activities in a Typical Cd-Contaminated Purple Field Soil, Southwestern China - Wenqiang Wang; Fengwu Zhou; Yajun Chang; Jian Cui; Dongyi He; Jinmeng Du; Andy Chan; Dongrui Yao; Yong Li; Zhiyuan Chen; Khalil Kariman (Bulletin of Environmental Contamination and Toxicology, 2020)

The formation of porphyry copper deposits - Weidong Sun; Jin-tuan Wang; Li-peng Zhang; Chan-chan Zhang; He Li; Ming-xing Ling; Xing Ding; Cong-ying Li; Hua-ying Liang (Acta Geochimica, 2017)

Interaction mechanism of pepsin with a natural inhibitor gastrodin studied by spectroscopic methods and molecular docking - Jie Wang; Calvin Chan; Feng-wen Huang; Jiang-feng Xie; Hong Xu; Ka-wai Ho; Sheng-gang Zheng; Zhang-li Hu; Jun Lu; Zhen-dan He (Medicinal Chemistry Research, 2017)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Mechanical robustness of the calcareous tubeworm Hydroides elegans : warming mitigates the adverse effects of ocean acidification - Chaoyi Li; Yuan Meng; Chong He; Vera B. S. Chan; Haimin Yao; V. Thiyagarajan (Biofouling, 2016)

RANS simulation of neutral atmospheric boundary layer flows over complex terrain by proper imposition of boundary conditions and modification on the k-ε model - B. W. Yan; Q. S. Li; Y. C. He; P. W. Chan (Environmental Fluid Mechanics, 2016)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Insights into the Substrate Specificity, Inhibitors, Regulation, and Polymorphisms and the Clinical Impact of Human Cytochrome P450 1A2 - Shu-Feng Zhou; Li-Ping Yang; Zhi-Wei Zhou; Ya-He Liu; Eli Chan (The AAPS Journal, 2009)

Cloning, characterization and expression analysis of a CXCR1-like gene from mandarin fish Siniperca chuatsi - Chao Chen; Zhongsheng Li; Zhicheng Zhou; Zhixin Yin; Siu-Ming Chan; Xiao-Qiang Yu; Shaoping Weng; Jianguo He (Fish Physiology and Biochemistry, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)